PENGARUH PENDIDIKAN KESEHATAN DENGAN METODE AUDIOVISUAL TERHADAP PENGETAHUAN, SIKAP, DAN PERILAKU PERSONAL HYGIENE DALAM PENCEGAHAN KEPUTIHAN - Trisetiyaningsih, Yanita; Nursanti, Ida (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2021)
ABSTRACT Background: At puberty, young women will experience an increase in the hormone estrogen, allowing adolescents to experience vaginal discharge. Leucorrhoea can be caused due to wrong habits in doing personal hygiene. In Indonesia in 2013 there were 237,641,326 cases of adolescents who experienced vaginal discharge (75%) Based on statistical data in Indonesia in 2008, of 43.3 million adolescents aged 15-24 years of unhealthy behavior which is one of the causes of leucorrhoea According to static data in the Special Region of Yogyakarta in 2009 the number of teenagers 2.9 million people aged 15-24 years 68% experience vaginal discharge Objective: Knowing the effect of health education with audiovisual methods on knowledge, attitudes, and personal hygiene behavior in preventing vaginal discharge. Methods: This research was conducted at SMP Negeri 1 Gamping for class XIII and IX. Data collection begins with conducting a pretest, providing health education with audiovisual methods, and posttest. The data obtained will be performed univariate analysis and bivariate analysis using the Wilcoxon Signed Rank Test. Result: the average score of knowledge level of pre-test vaginal discharge was 80.7 and posttest was 85.4. The mean score of the pretest prevention attitude was 80.3 and the posttest was 86.4, the pretest behavior average score was 77.8 and the posttest behavior was 79.6. Conclusion: Audiovisual health education has an influence on the level of knowledge, attitudes and behavior of adolescents in preventing vaginal discharge.